Factors influence attitude towards online shopping of MiCoST students / Muhammad Aizat Afiq Abd Jalil - Abd Jalil, Muhammad Aizat Afiq (Faculty of Business and Management, 2018)
This project report presents the project Factors Influence Attitude Towards Online Shopping of MiCOST Students. My project is to develop system for Student in Melaka International College of Science and Technology .The objective of this project is to know the attitude and behavior of cutomers after they have use online among MiCOST students where in specifically Faculty of Information and Technology. The report initially identifies and analyses the attitudes towards online shopping objectives of the project to be implemented. This research can give advantages because after know the result from collect the data from MiCOST students the company can improve their services to customers.